sqrt(7x + 29) = x + 3
square both sides
7x + 29 = (x + 3)^2
7x + 29 = (x + 3)(x + 3)
7x + 29 = x^2 + 3x + 3x + 9
7x + 29 = x^2 + 6x + 9
x^2 - x - 20 = 0
(x - 5)(x + 4) = 0
x = 5 or -4
2006-10-05 11:35:28
·
answer #1
·
answered by Sherman81 6
·
0⤊
1⤋
ok, it really is what I get up with: (7X + 29)^(a million/2) = X + 3 sq. both section 7X + 29 = (X+3) (X+3) then, 29 = X^2 + 6X - 7X + 9 29 = X^2 -X + 9, hence: 0 = X^2 - X + 9 -29 0 = X^2 - X - 20 hence, (X - 5) (X + 4) = 0 The roots are 5 and -4 make sure your answer by skill of technique of plugging the roots again into the unique equation and seeing if the answer is fairly.
2016-11-26 19:47:57
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
Here's the original question:
√(7x+29) = x+3
To remove the root sign, square both sides:
7x + 29 = (x+3)(x+3)
Multiply through:
7x + 29 = x² + 6x + 9
Group it all on one side:
x² -x -20 = 0
Factor it:
(x - 5)(x + 4) = 0
x = 5 or x = -4
Double check the answers by plugging in your answers.
x = 5
√(7(5) + 29) =? (5) + 3
√(35 + 29) =? 8
√64 =? 8
8 = 8 <-- check, so x = 5 is correct
x = -4
√(7(-4) + 29) =? (-4) + 3
√(-28 + 29) =? -1
√1 =? -1 (√1 = ±1) <-- check, so x = -4 is correct
The answers for x are:
x = 5
x = -4
2006-10-05 11:34:32
·
answer #3
·
answered by Puzzling 7
·
0⤊
0⤋
Just square both sides to get (7x+29) = (x+3)^2 and solve via the quadratic formula or factoring.
2006-10-05 11:35:23
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Square both sides:
7x+29=(x+3)^2 = x^2+6x+9.
Move everything to one side:
x^2+6x-7x+9-29=0, which simplifies to
x^2-x-20=0.
Factor:
(x+4)(x-5)=0,
so x=-4 or x=5.
2006-10-05 11:33:55
·
answer #5
·
answered by James L 5
·
0⤊
1⤋
Just square both sides to get 7x+29=(x+3)^2=x^2+6x+9
x^2-x-20=0
(x-5)(x+4)=0
x=5,-4
2006-10-05 11:39:49
·
answer #6
·
answered by bruinfan 7
·
0⤊
1⤋
ok im in algebra right now and we just did problems like this...
First you find the square root of 7 which is 2.6
2.6x+29=1x+3 (it is easier with the 1 in there)
then minus the 1x one each side with like terms
2.6x+29=1x+3
- 1x -1x (the second -1x is soposed to go under the top 1x but i can't get it to go there)
equals
1.6x=3
then you have to divide 3 by 1.6x because 1.6x has the variable so...
1.6x/1.6=3/1.6
x=1.9 (rounded with out rounding would be 1.875)
so if you were solving for x, x equals 1.9
2006-10-05 11:56:33
·
answer #7
·
answered by jesusfreak92092 1
·
0⤊
1⤋
squaring both sides
7x+29=x^2+6x+9
=>x^2-x-20=0
(x-5)(x+4)=0
x=5 or -4
2006-10-05 11:36:02
·
answer #8
·
answered by raj 7
·
0⤊
1⤋
I think you might want to be careful about that -4 as a root since it doesnt fit into the original problem
2006-10-05 11:38:38
·
answer #9
·
answered by Greg G 5
·
1⤊
0⤋
squaring both sides of the equation was pretty obvious, the rest is too much work for me
2006-10-05 11:38:50
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋